2022
DOI: 10.3390/f13050797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Ring Width and Latewood Content on Selected Physical and Mechanical Properties of Plantation Japanese Larch Wood

Abstract: In order to evaluate the physical and mechanical properties of plantation Japanese larch wood, various physical and mechanical indicators were measured with reference to Chinese national standards. The characteristics of the growth ring on the end face of wood samples were captured, with the mean latewood percentage being 21.4% and the mean ring width being 3.24 mm. Relationships between growth ring characteristics, latewood percentages, and the physical and mechanical properties of the plantation Japanese lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Figure 5a shows the relationship between latewood rate an growth ring width. The latewood rate in our case decreased as growth ring width in creased, as also observed by Wang Sidong [27]. The transverse compressive strength wa fitted with the growth ring width and the latewood rate.…”
Section: Effect Of Growth Ring Width On Transverse Compressive Strengthsupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 5a shows the relationship between latewood rate an growth ring width. The latewood rate in our case decreased as growth ring width in creased, as also observed by Wang Sidong [27]. The transverse compressive strength wa fitted with the growth ring width and the latewood rate.…”
Section: Effect Of Growth Ring Width On Transverse Compressive Strengthsupporting
confidence: 88%
“…The growth ring width can be used to evaluate the physic and mechanical properties of wood [19][20][21][22][23][24]. Some studies have shown a negative correl tion between the modulus of rupture (MOR) and modulus of elasticity (MOE) of woo which can be used to predict bending performance [25][26][27]. Different positions even o the same log can also have very different physical properties [28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…Conifers consist mainly of axial tracheids, serving for support and for transport of water and dissolved minerals. Their anatomical structure, chemical composition, and the spatial arrangement of polymers in the wood cell walls determine the mechanical properties [3][4][5]. Conifers contain two main types of tracheids: earlywood (EW) tracheids, which have thin cell walls and large cell cavities, and latewood (LW) tracheids, which have thick cell walls and small cell cavities.…”
Section: Introductionmentioning
confidence: 99%